Occupational safety and health among fishing boat workers in Thailand - Hasamoh, Alisa; Wichaidit, Wit (Intelektual Pustaka Media Utama, 2024)
The Thai fishing industry has been under close scrutiny for conditions faced by fishing boat workers, yet data are scarce with regards to occupational safety and health (OSH) among its workers. The objectives of this study are to describe: i) water, sanitation, and hygiene (WASH) conditions, and; ii) OSH conditions faced by migrant fishing boat workers in Thailand. We conducted a mixed-methods study with a quantitative survey in 200 migrant fishing boat workers and focus group discussions with 11 workers and 6 stakeholders in southern Thailand. We analyzed quantitative and qualitative data using descriptive statistics and content analysis, respectively. Nearly all participants (95.0%) reported that drinking water on board was stored in a sealed container, but only 5.5% of participants reported that there was latrine on board for defecation. Nearly all participants reported proper storage of objects on board, although findings on maintenance varied. Use of personal protective equipment was scarce as equipments obstruct the workers’ movement. The findings highlighted areas where improvements in WASH and OSH are needed. However, caveats regarding potential information bias and lack of generalizability should be considered in the interpretation of the study findings.